Autonomy as license to operate: Establishing the internal and external conditions of informed choice in marketing. (December 2020) - Anker, Thomas
The assumption that consumers voluntarily accept or decline marketing offerings provides the ethical justification that gives marketing as a social system its license to operate. Consumer autonomy is, therefore, the key ethical principle of marketing in capitalistic economies. However, even in domains with extensive regulatory frameworks and advanced market conditions, consumers are often ill-informed or underinformed. The resultant lack of epistemic confidence diminishes consumers' ability to make informed choices. At the same time, consumers are by default exposed to promotional content designed to persuade them to accept marketing offerings. This threatens personal autonomy. We develop a concept of consumer autonomy which marketing regulations should protect and promote to enhance informed decision-making. We design autonomy to be robust in situations where individuals are exposed to persuasive attempts to influence them to choose a specific course of action. As such, our concept of autonomy is applicable to a range of contexts beyond marketing where it is necessary to balance external influences and individual autonomy.